Curriculum and Student Analysis of Interactive Electronic Book Based on Project in Strategy and Design of Learning Subject - Diana Susanti; Vivi Fitriani; Liza Yulia Sari (Postgraduate, University of Mataram, 2021)
Biology learning strategies and designs are courses that teach the principles of learning and teaching and apply them in the biology learning process. So far, students only use printed textbooks as a reference. This is not in accordance with the existing needs, because students are more likely to look for teaching materials from the Internet. This results in learning to be monotonous, not interactive and does not increase student creativity. It is for this reason that researchers develop project-based interactive books so that learning becomes interactive and can increase student creativity. The purpose of this research is to determine the curriculum analysis and student analysis in the development of project-based interactive books. This research is a development research using the 4D model at a specified stage. The analysis data were obtained through descriptive analysis. The resulted showed that 10 materials need to be developed in the module. Can prove that there are ten materials developed. It can be concluded that there are ten materials developed in project-based interactive digital books and the age range of students is 18-21 years